Women's satisfaction with intrapartum care in St Paul's Hospital Millennium Medical College Addis Ababa Ethiopia: a cross sectional study - Tangute Demas; Tewodros Getinet; Delayehu Bekele; Teshome Gishu; Malede Birara; Yemesrach Abeje (BMC, 2017)
Abstract Background Satisfaction during intrapartum care is the most influential attribute on maternal health service return behaviors and utilization. Measuring satisfaction of women with intrapartum care helps to address the problems and improves the quality of delivery services. The aim of this study is to assess women's level of satisfaction during intrapartum care. Method A hospital based, analytic, cross sectional study was conducted at St. Paul's Hospital Millennium Medical College (SPHMMC), Addis Ababa Ethiopia, from May to June 2015. Data collectors administered a structured and pretested questionnaire to collect data and then analyzed it using SPSS version 20.0 software. Binary logistic regression was used to identify factors associated with women's intrapartum care satisfaction. Result A total of 394 women of mean age 25.98 years with a standard deviation of ±4.72were included in the study. Only 19% of the women were satisfied with the intrapartum care they received. The variables which were significantly associated with satisfaction of intrapartum care were; opportunity to talk Adjusted Odds Ratio (AOR) (95% CI) 2.44 (1.12, 5.29); Pain Management AOR (95% CI) 3.37 (1.83, 6.21); Short Length of Time Taken for Admission After Seen by Health Professionals AOR (95% CI)0 .97 (0.93, 0.99), and Short Length of Stay in the Hospital AOR (95% CI) 0.91 (0.87, 0.96). Conclusions The women's overall satisfaction with intrapartum care was low. Multiple factors influence their satisfaction. Health professionals, policy makers and health administrators should give emphasis to factors that contribute to low satisfaction of women with intrapartum care. They should also strengthen their efforts to deliver quality and easily accessible maternal health service to improve women's overall satisfaction with the maternal health service.